(untitled) (Huellas, 2018)
This article aims at analyzing the concept of territory in the Peruvian Amazonia and the existing power relations as control mechanisms and colonial / modern domination. We apply categories of analysis of sociology and geography, such as: territory, power, de-re territorialization and coloniality of power, in order to reflect on the presence of the colonial / modern State as a legitimating instrument of any process / action of violence and appropriation of the Amazon territory, that the colonial / modern capital needs in order to continue with its process of accumulation. To achieve this purpose, a bibliographic review was made on the aforementioned categories and the data collected in the field was analyzed for the period from 2015 to 2017, as part of the theoretical debate of my Master’s Thesis. This article tries to make a contribution to geographic thought through the critical analysis of the territory and the coloniality / modernity concepts present in the forms of organization of the Peruvian Amazon territory.